1981
DOI: 10.1007/bf00252696
|View full text |Cite
|
Sign up to set email alerts
|

More about carbohydrates

Abstract: Letters to the Editor Is Diabetes Responsible for an Increase of the Mean Red Cell Volume? Dear Sir, The Short Communication of Davidson et al. [1] deserves some comment: The authors, who reported a higher mean red cell volume (MCV) in a group of 100 diabetic patients compared with a control group, were asking other investigators to contribute to the understanding of this result. We would like to make the following suggestions based on studies that we have carried out. We studied the MCV values in two populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the 1979 policy statement, the ADA recommended reducing the intake of fat and increasing that of complex carbohydrates to -5 0 % of the total calories with the ingestion of foods high in fiber as desirable (2). Dietary advice to patients with diabetes continues to emphasize the virtues of complex carbohydrates rich in fiber, but the dogma is coming under closer scrutiny and remains a controversial issue (3)(4)(5)(6). These diets are substantially different from the average American diet, and it has been suggested that they may not be effective if the insulin secretory capacity is compromised.…”
mentioning
confidence: 99%
“…In the 1979 policy statement, the ADA recommended reducing the intake of fat and increasing that of complex carbohydrates to -5 0 % of the total calories with the ingestion of foods high in fiber as desirable (2). Dietary advice to patients with diabetes continues to emphasize the virtues of complex carbohydrates rich in fiber, but the dogma is coming under closer scrutiny and remains a controversial issue (3)(4)(5)(6). These diets are substantially different from the average American diet, and it has been suggested that they may not be effective if the insulin secretory capacity is compromised.…”
mentioning
confidence: 99%
“…Diet is a basic factor in the treatment of diabetes. Nevertheless, recent controversies concerning the composition of the diet in diabetes have highlighted the relative paucity of experimental data or clinical studies on this subject [17,20,21,32,33,37]. A conclusion from some recent studies is the favourable effect of a high dietary fibre intake, which improves tolerance to carbohydrates and ensures a better metabolic control of diabetes [1,2,6,13,29,30,34,[41][42][43]47].…”
mentioning
confidence: 99%
“…However, in this later study the source of the carbohydrate energy (sucrose vs corn syrup) did have an effect with sucrose-containing diets requiring lower insulin concentrations to maintain euglycemia than did the corn syrup-contain ing diets. Nevertheless, the issue of how much carbohydrate should be in the diabetic diet remains controversial [8,9].…”
Section: Datementioning
confidence: 99%